On the Future of Portuguese Physician-Scientists - Soares, Célia Azevedo; Incio, João; Ferreira, Miguel Reis; Barbosa-Breda, João; Páris, Liliana; Sandoval, José Luís (Acta Médica Portuguesa, 2016)
N/A.